Figurative Images and Their Iconographic Prototypes in Decoration of Scabbard and Gorytos Overlays from Scythian Tombs of the 4th Century BC - Galdanova, Oyuna A. (Actual Problems of Theory and History of Art, 2016)
The Attic, Peloponnesus and Asia Minor monumental sculpture of the 5th and 4th centuries BC such as reliefs of Parthenon, temple of Athena Nike, Erechtheum, attic gravestones, reliefs of temple of Apollo Epicurius at Bassae, Heroon of Gjolbaschi, the Nereid Monument at Xanthos and the Mausoleum at Halicarnassus, are recognized in the research as iconographic prototypes of the images of Chertomlyk and Vergina group scabbard and gorytos decoration. What is more, there are a few consistencies of these adoptions. First of all, craftsmen could both replicate iconographic scheme and loosely treat gures in adopted motives. Roles of characters and circumstances of their depiction remain the same, as well as their a liation with Greeks or barbarians, although the same iconography was used for depicting gures of Amazons on monumental sculpture and male gures on toreutic pieces. In addition, cra smen had to take into account a “non-Greek” attitude of barbarian customers to nude gures.
Keywords: Greco-Scythian style; gorytoi; scabbard; iconographic prototypes; toreutics